ERK1-mediated GLYCTK2 phosphorylation promotes fructolysis to sustain glioblastoma survival under glucose deprivation - Yingping Li; Fenna Zhang; Fumin Hu; Rui Tong; Yueqi Wen; Guokai Fu; Xueli Bian (Cell Death Discovery)
Abstract Metabolic plasticity sustains glioblastoma (GBM) survival under nutrient stress, yet how fructolytic adaptation compensates for glucose deprivation remains unclear. Here, we identify glycerate kinase 2 (GLYCTK2) as a glucose-sensing metabolic checkpoint that maintains GBM cell viability through ERK1-mediated phosphorylation. Mechanistically, glucose deprivation-activated ERK1 phosphorylates GLYCTK2 at serine 220 directly, which prevents STUB1 (ubiquitin E3 ligase) binding, thereby abrogating the ubiquitination and degradation of GLYCTK2. Importantly, Functional studies demonstrated that fructose supplementation rescues glucose deprivation-induced death in wild-type GBM cells, but fails to protect GLYCTK2-depleted cells, establishing GLYCTK2 as the gatekeeper of fructolytic salvage pathways. These findings demonstrate an important mechanism by which GBM cells rewire glucose metabolism to fructose metabolism via phosphorylating and stabilizing GLYCTK2 to maintain GBM cell survival under glucose deprivation condition, underscoring the potential to target GLYCTK2 for the treatment of patients with GBM.